Comparison of biodegradable and durable polymer drug-eluting stents in acute coronary syndrome: a meta-analysis - Tingting Wei; Can Huang; Yifan Zeng; Haoyong Yuan; Zhongshi Wu; Ting Lu; Yalin Liu (BMJ Open)
Objective To compare the safety and effectiveness between biodegradable polymer drug-eluting stents (BP-DES) and durable polymer drug-eluting stents (DP-DES) in patients with acute coronary syndrome (ACS).Design Meta-analysis of randomised controlled trials (RCTs).Primary and secondary outcome measures Major adverse cardiovascular events (MACEs) were considered the primary endpoint. Efficacy endpoints included target vessel revascularisation (TVR) and target lesion revascularisation (TLR). Safety endpoints included all-cause death, cardiac death, target vessel myocardial infarction and stent thrombosis (ST).Methods We searched PubMed, Medline, Embase and the Cochrane Controlled Register of Trials for comparative studies of BP-DES and DP-DES in patients with ACS from January 2000 to July 2021. Statistical pooling was performed to estimate incidence using a random-effects model with generic inverse-variance weighting. Risk estimates were computed with 95% CIs.Results Eight articles with seven RCTs that compared BP-DES and DP-DES in patients with ACS were identified and included in the qualitative and quantitative analyses. There was no difference in the baseline characteristics, except for the number of smoking patients (OR: 1.13, 95% CI 1.03 to 1.24; p=0.008, I2=29%), which was significantly lower in the BP-DES group. The meta-analysis demonstrated that MACEs, efficacy endpoints and safety endpoints were similar between the groups at 1 year. However, the incidence of total ST was signiﬁcantly different between the BP-DES and DP-DES groups in the follow-up period (p=0.0001). Further analysis showed a statistically significant difference in MACEs (OR: 0.71, 95% CI 0.57 to 0.88; p=0.002, I2=0 %), TLR (OR: 0.71, 95% CI 0.51 to 1.01; p=0.05, I2=0%), TVR (OR: 0.70, 95% CI 0.52 to 0.94; p=0.002, I2=15%), total ST incidence (OR: 0.59, 95% CI 0.46 to 0.77; p=0.0001, I2=48%) and ST incidence (OR: 0.63, 95% CI 0.47 to 0.85; p=0.002, I2=0%) over 2 years.Conclusion This meta-analysis revealed that both stent types demonstrated excellent safety and efficacy profiles at 12 months. However, a slight increase in MACEs, TLR, TVR and ST incidence was observed in the DP-DES group over the 2-year follow-up period, suggesting that BP-DES may be more favourable when treating patients with ACS.Trial registration number NCT00389220.